Sistem Informasi E-Commerce Untuk Penjualan Barang Berbasis Mobile Web - Cindi Wulandari; Tri Hasanah Bimastari Aviani; Anisah Julianti (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
The positive impact of advances in information technology has been felt through the various conveniences provided, maximizing every organizational activity. One example is the use of information technology, especially the use of the internet in government activities. It has become an electronic information medium that plays an important role in improving services to the community. Information technology, as a means of managing data, enables government agencies and organizations to achieve their goals more efficiently. Good use of information technology can provide better services for the problems faced by private companies and government agencies.E-Commerce, as a form of online marketing and sales, has become a relevant strategy for every business. DefinitionE-commerce is the process of buying and selling transactions via the internet, with the website as the main platform for carrying out the process. Businesses such as Toko Ratna Siahan, which sells household appliances, electronics and kitchen equipment, are lookingE-Commerce as an attraction because it can provide better information. Even though Toko Ratna Siahan has superior products in kitchen equipment, consumer demand continues to increase. To overcome this challenge, Toko Ratna Siahan needs to innovate. However, the sales transaction system which is still manual is an obstacle, including the lack of storage and processing of sales transaction data, promotions which are still traditional in nature, and the absence of online sales. To overcome this problem, system implementation is neededE-Commerce. This system will provide comprehensive information about the goods being sold and enable direct sales transaction processes. The aim is to increase the effectiveness of the services provided by the Ratna Siahan Store and help maximize the marketing process and sales transactions, overcoming the obstacles faced by the store.